Yes-associated protein regulates autophagy to restore skin barrier function in atopic dermatitis - Jia, Jinjing; Ma, Xin; Wang, Tongfei; Ye, Siqi; Yan, Fenggen; Liu, Junfeng; Li, Hongyi; Chen, Dacan; Mo, Xiumei (Frontiers in Immunology, 2025)
IntroductionAtopic dermatitis (AD) is characterized by skin barrier dysfunction and inflammation.This study explored the relationship between Yes-associated protein (YAP) expression, autophagy, and skin barrier dysfunction in AD.MethodsSkin samples from AD patients and healthy controls were analyzed using mRNA-seq. Differential gene expression was visualized using ggplot2 and analyzed using GO and KEGG pathway analyses. An AD mouse model was created using house dust mite ointment, and HaCaT cells were treated to mimic AD inflammation. YAP expression was transfected with lentivirus in vivo and siRNA in vitro. Autophagy was induced with rapamycin.ResultsYAP levels were reduced in AD patients and correlated with filaggrin (FLG). YAP overexpression in mice improved skin lesions, enhanced barrier function (increased FLG, involucrin, and loricrin), and promoted autophagy (increased LC3-II/I; decreased p62 and p-mTOR). Similar effects were observed in cells, with increased proliferation and reduced apoptosis. YAP knockdown reversed these effects, which were mitigated by rapamycin.DiscussionReduced YAP expression in AD is linked to inflammation and barrier dysfunction. YAP may improve AD by enhancing autophagy, reducing inflammation, and restoring skin barrier function.